Aerospace series. Bolts, shouldered, thin hexagonal head, close tolerance shank, short thread, in titanium alloy, anodized, MoS2 coated. Classification: 1 100 MPa (at ambient temperature)/315 °C. (4th November 2019) - British Standards Institution,
No abstract available